A BROAD OVERVIEW OF THE AVIFAUNA OF SECONDARY FORESTS IN PERUVIAN AMAZONIA - ESTEVES, Juan (2024)
In the Peruvian Amazon, we conducted an extensive survey of bird species in six secondary forests. We used the point count method and established 360 survey points (60 in each zone) at least 500 meters away from the others. These observations covered six zones across nine departments, including Loreto, Amazonas, San Martín, Ucayali, Huánuco, Pasco, Junín, Cusco, and Puno, at altitudes ranging from 96 to 2501 meters. We assessed these forests in both dry and rainy seasons with two consecutive days of observations at each point. Our findings revealed high species richness in every zone, with a total of 628 bird species identified, including one Endangered, and five Vulnerable according to the IUCN. Passeriformes was the order with the most species registered, while Tyrannidae and Thraupidae were the most species-rich families. Zones within protected areas exhibited higher species richness compared to adjacent unprotected zones. These results highlight the crucial role of secondary forests in conserving a significant number of bird species despite compositional changes.